c=[(20+4):6-4]*35+2*(5*15-2*3*5)=
Răspunsuri la întrebare
Răspuns de
3
c= (24:6-4) • 35+2 • (5•15-2•3•5)
c= (4-4)•35+2•(75-30)
c= 0•35+2•45
c= 0+90
c= 90
c= (4-4)•35+2•(75-30)
c= 0•35+2•45
c= 0+90
c= 90
alex13miha:
coroana??
Răspuns de
1
(24:6-4)*35+2*(5*15-2*3*5)
(4-4)*35+2*(5*15-2*3*5)
0*35+2*(5*15-2*3*5)
0+2*(5*15-2*3*5)
2*(75-6*5)
2*(75-30)
2*45=90
(4-4)*35+2*(5*15-2*3*5)
0*35+2*(5*15-2*3*5)
0+2*(5*15-2*3*5)
2*(75-6*5)
2*(75-30)
2*45=90
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă